La Diócesis de Nicaragua y Costa Rica: su conformación y sus conflictos, 1531-1850 - Velázquez Bonilla, Carmela (2004)
This work sets forth an analysis made of the Nicaraguan and Costa Rican Diocese (1531-1850) from its creation up to its division in 1850. It was established based on the resolutions of the Royal Patronage (Patronato Real) and the accords of the Council of Trent (1545). Likewise, research is carried out on the role played by the bishops that geared the Diocese, as well as on the internal conflicts, especially those that occurred in the province of Costa Rica.